2016
DOI: 10.1038/srep22152
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene emissions from Alternaria alternata and Fusarium oxysporum: Effects of age, nutrient availability and co-cultivation

Abstract: Alternaria alternata is one of the most studied fungi to date because of its impact on human life – from plant pathogenicity to allergenicity. However, its sesquiterpene emissions have not been systematically explored. Alternaria regularly co-occurs with Fusarium fungi, which are common plant pathogens, on withering plants. We analyzed the diversity and determined the absolute quantities of volatile organic compounds (VOCs) in the headspace above mycelial cultures of A. alternata and Fusarium oxysporum under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 55 publications
2
57
1
Order By: Relevance
“…alternata emits highly reactive VCs such as sesquiterpenes (Weikl et al, 2016). These compounds are known to function as infochemicals, playing crucial roles in plantmicrobe interactions (Peñuelas et al, 2014;Ditengou et al, 2015).…”
mentioning
confidence: 99%
“…alternata emits highly reactive VCs such as sesquiterpenes (Weikl et al, 2016). These compounds are known to function as infochemicals, playing crucial roles in plantmicrobe interactions (Peñuelas et al, 2014;Ditengou et al, 2015).…”
mentioning
confidence: 99%
“…VOCs were collected for 6 h from sealed Petri dishes by headspace sorptive extraction using the stir bar sorptive extraction method with Gerstel Twisters (Gerstel GmbH & Co. KG, Mülheim an der Ruhr, Germany) as described in [33]. The samples were analysed with a thermo-desorption unit (Gerstel GmbH & Co) coupled to a gas chromatograph-mass spectrometer (GC-MS; GC model: 7890A; MS model: 5975C; Agilent Technologies, Santa Clara, CA, USA) as described in [34]. The chromatograms were analyzed by the enhanced ChemStation software (MSD ChemStation E.02.01.1177, 1989–2010 Agilent Technologies, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to soluble phytohormones, fungi also emit species-specific blends of VOCs. The emission intensity as well as the VOCs composition depends strongly on physiological as well as environmental factors [33,34]. Recently, it was shown that plants could sense fungal emitted sesquiterpenes [32,35]; the airborne plant-fungal communication through the sesquiterpene thujopsene was suggested to prepare the plants for mycorrhizal symbiosis [32].…”
Section: Introductionmentioning
confidence: 99%
“…The shifts in fungalassociated bacterial community led to shifts in volatile production of the original and the The composition and abundance of volatiles was affected by the nutrient conditions with more volatiles produced on the nutrient-rich PDA media. Several independent studies have reported that the volatile profiles of bacteria and fungi are strongly dependent on growth conditions, interactions and nutrient availability (Garbeva et al 2014b;Tyc et al 2015;Schmidt et al 2016;Weikl et al 2016). Hence, it is questionable whether the same volatile-mediated interactions will occur in nature under nutrient-limited conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Weikl et al 2016), an important biotic factor affecting the blend of bioactive VOCs released in soil is the direct interplay between soil shown that the fungal terpene 3-carene stimulated bacterial motility at low concentrations while high concentrations inhibited motility (Schmidt et al 2016). On the other hand, the biological activity of VOCs can be enhanced by synergistic effects between different volatile compounds (De Vrieze et al 2015;Mookherjee et al 2017) or volatile and non-volatile compounds (Tyc et al 2017a;Tyc et al 2017b).…”
Section: Factors Influencing the Composition And Biological Activity mentioning
confidence: 99%